Hubungan Electronic Word of Mouth Di @theswoonnetflix Dengan Minat Berlangganan Netflix - Aulia Rahma Fadilla; Adi Nugroho; Nurist Surayya Ulfa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
Netflix made a new innovation with The Swoon, a community for fans of Korean Netflix shows around the world. Using Instagram to share things about Netflix’s Korean shows, The Swoon has succeeded in sparking online conversations or e-WOM. E-WOM has several dimensions, including intensity that related to involvement in e-WOM, content of e-WOM itself that related to attractiveness and positive valence. Even though it has succeded in triggering e-WOM, Netflix subscribers in Indonesia are still less than some other competitors. In fact, Netflix has several times failed to reach its target of increasing new subscribers and losing subscribers globally. The purpose of this research is to find out whether there is a relationship between involvement intensity, attractiveness and positive valence on electronic word of mouth at @theswoonnetflix with Netflix subscription intention. The population in this explanatory quantitative research is men and women who live in Indonesia, follow @theswoonnetflix on instagram, have seen or been involved in talks about Netflix and its Korean shows on @theswoonnetflix account, aged 18 – 44 years, and have never or not currently subscribed Netflix. The sample that used is 100 respondents with nonprobability sampling technique. The theory used is the Buyer’s Information Environment Theory. The test results using Kendall’s tau-b correlation test show the relationship between involvement intensity on e-WOM at @theswoonnetflix with Netflix subscription intention has a significance value of 0,000 which means it’s very significant and has the correlation coefficient of 0,690 which means both of them have a strong level of relationship. Then, the relationship between e-WOM attractiveness on @theswoonnetflix with Netflix subscription intention also has a significance value of 0,000 or very significant and has the correlation coefficient of 0,685 which means both of them have a strong level of relationship. Furthermore, the relationship between e-WOM positive valence on @theswoonnetflix with Netflix subscription intention has a significance value of 0.000 which means it’s very significant and has the correlation coefficient of 0.601 which means both of them have a strong relationship. All of the correlation coefficients from the three correlation tests above are positive, indicating a unidirectional relationship.